Brucellosis control in northeast China: a long way to go. Issue 8 (August 2015) - Zhang, X.; Wang, Z.; Mu, G.; Wang, T.
Highlights Currently northeast China appeared to be the worst hit area by brucellosis in China. This manuscript makes clear the causes for the brucellosis spread in northeast China. Brucellosis prevention and control in northeast China would be a complex systematic project.